Analisis Perilaku Konsumen Dalam Keputusan Pembelian Roti Pada Toko Mama Kanae Bakery - Viola Natadoan Randalayuk; Isak Pasulu; Olivia D.Y. Pompeng (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze consumer behavior in the decision-making process of purchasing bread at Mama Kanae Bakery. The research method employed is a survey conducted through interviews with the store's customers. Data were collected from respondents who are active consumers of Mama Kanae Bakery. The analysis results indicate that psychological factors play the most significant role in the decision-making process of purchasing bread at the store. Factors such as perceived product quality, taste value, and brand value have a significant impact on consumer purchasing decisions. Additionally, brand image and previous experiences are also key factors influencing consumer perceptions of bread products at Mama Kanae Bakery.